Aktywność fosfatazy zasadowej w glebach rozwijających się z gruntów pogórniczych = The alkaline phosphatase activity in soils orginating from post mining grounds - Gilewska, Mirosława; Płóciniczak, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The most dynamic decomposition of phosphorus organic combination measured by the activity of phosphates base takes place in the soil which undergoes fodder-cereal usage system and Lucerne is the basis for cultivation. The phosphates activity varied depending on the level of fertilization from 87-132 mmol PNP .kg-1 soil. ha-1.The decomposition of phosphorus components in the soil on which rape and wheat was cultivated alternately was considerably slower.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); fosfataza alkaliczna; grunt pogórniczy; gleba; system użytkowania; alkaline phosphates; post mining grounds; soils; usage system